Knockdown of STAT3 targets a subpopulation of invasive melanoma stem‐like cells. (30th April 2019) - Kulesza, Dorota W; Przanowski, Piotr; Kaminska, Bozena
Abstract: Transcription factor signal transducer and activator of transcription 3 (STAT3) is constitutively activated in many cancers, including melanomas. Active, phosphorylated STAT3 contributes to tumor growth and formation of the immunosuppressive tumor microenvironment. Recent evidence suggests an important role of STAT3 in self‐renewal of cancer stem‐like cells (CSCs). In the present study, we aimed to determine the expression and role of active STAT3 in melanoma CSCs. We found the increased levels of phosphorylated (Y705) STAT3 in CSC sphere cultures derived from three human and murine melanoma cells. Knockdown of STAT3 did not affect basal proliferation, but reduced sphere forming capacity of two human melanoma cell lines. Moreover, the level of active STAT3 was elevated in rhodamine 123 negative subpopulations of CSCs sorted from three melanoma cell lines. We found that focal adhesion kinase (FAK) and AKT signaling pathways, implicated in the regulation of cell migration and invasion, were up‐regulated in melanoma CSCs. Moreover, expression of SERPINA3, which regulates melanoma invasion, was increased in melanoma CSCs sphere cultures, which correlated with augmented cell invasion in Matrigel. Our findings show that STAT3 is activated and supports maintenance of melanoma CSCs. It suggests that STAT3 could serve as a potential target to impair tumor progression or recurrence.